Views of pre-service biology teachers on structured grid - Daşdemir, İkramettin (Journal of Turkish Science Education, 2016)
Research was carried out to identify pre-service biology teachers’ views on ‘structured grid’, one of the alternative assessment and evaluation tools available to teachers. A questionnaire form, consisting of four openended questions, was used as a data collection tool. Changes were made to the questionnaire to take into account the opinions of two faculty members and two teachers. The sampling of the study consisted of 29 pre-service biology teachers enrolled on a teacher training course at the Education Faculty at Ordu University during the 2014-2015 academic year. A case study was utilized in the study. The data obtained were examined by means of inductive content analysis. Based on the findings obtained from the open-ended questionnaire, the pre-service biology teachers stated that the use of structured grid, one of the alternative assessment and evaluation tools, in a biology course would contribute towards improved learning of the subject and would have a positive effect on the identification and elimination of misconceptions. Moreover, it was found that it eliminated students’ weaknesses, raised students’ curiosity and facilitated teachers’ work. It allowed subjects to be taught in a fun way, it enabled student participation and it provided learning retention. Moreover, the findings highlighted that teachers did not adequately use alternative assessment and evaluation tools that these activities were not included in the course books to a sufficient degree and that teachers wanted to use these activities. It was suggested at the end of the study that all the teachers working for the Ministry of National Education should be introduced to alternative assessment and evaluation tools and that they should also be given in-service training on how to use them and how to evaluate students with these tools. Another finding of the study revealed that pre-service teachers must acquire knowledge, skills and understanding of alternative assessment and evaluation tools and activities in their educational process.
Keywords: : Pre-service teachers; Structured; Assessment and Evaluation